2019
DOI: 10.1097/md.0000000000015368
|View full text |Cite
|
Sign up to set email alerts
|

The influence of statins on aortic aneurysm after operation

Abstract: Aortic aneurysm (AA) is a disease with substantially higher health care costs and very high mortality upon rupture. Statins have a non-lipid-lowering pleiotropic mechanism that may be beneficial for AA in disease progression and improvement of AA patient outcomes. Previous studies have been conducted with some limitations and without considering immortal time bias, lag time, and adherence. The aim of our study was to analyze the effect of statin use on AA postoperation after controlling for these factors.All p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…Post-treatment statin use, which was defined as persistent statin use 30 days after the procedure, was associated with a significantly lower mortality rate. However, only 12.2% (199/1633) of the whole study population were prescribed statins after AAA repair [22]. In our cohort, 38.1% (3386/8893) were using statins before EVAR and, among them, 81.7% maintained statin use after the procedure.…”
Section: Discussionmentioning
confidence: 63%
“…Post-treatment statin use, which was defined as persistent statin use 30 days after the procedure, was associated with a significantly lower mortality rate. However, only 12.2% (199/1633) of the whole study population were prescribed statins after AAA repair [22]. In our cohort, 38.1% (3386/8893) were using statins before EVAR and, among them, 81.7% maintained statin use after the procedure.…”
Section: Discussionmentioning
confidence: 63%
“…Another meta-analysis showed the long-term outcome bene it of stain therapy in patients with AAA without any signi icant impact on peri operative mortality [31]. This was also observed in another study done by Liao et al [32]. This bene it is derived due to the reduction in the in lammatory markers and the levels of the matrix metalloproteinases [33].…”
Section: Treatmentmentioning
confidence: 69%
“…63 Previous meta-analysis demonstrated that patients with statin treatment were associated with a decreased growth rate of AA. 64,65 Controversy also remains because of different clinical outcomes that some studies have indicated a beneficial association between statin use and the progression of AAA, [66][67][68][69] whereas others failed to draw the same conclusion as the former. 70,71 Therefore, there is not yet enough evidence supporting that statins act as effective pharmaceutical agents to stabilize AAA, although the benefits of statins are impressive on animal models.…”
Section: Statinsmentioning
confidence: 99%